Penerapan Media 3D Plastisin untuk Meningkatkan Pemahaman Siswa Kelas 5 SD pada Materi Sistem Pencernaan - Juhairiyah; Nur Khosiah; Yulina Fadilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The process of teaching natural sciences at the elementary education level faces challenges in presenting abstract concepts, such as the mechanism of the human digestive system, which requires a high level of visualization ability. This study aims to describe the implementation of a three-dimensional learning aid based on plasticine to improve mastery of the digestive system concept among fifth-grade students at MI Muhammadiyah 2 Probolinggo. This study employs a qualitative descriptive method with the science teacher and fifth-grade students as the research subjects. Data were collected through semi-structured interviews, participatory observation, and documentation, and were analyzed using the Miles and Huberman model. The findings indicate that the implementation of the 3D plasticine learning aid combined with thematic songs produced a significant transformation in classroom learning dynamics and students’ conceptual mastery. Students who were initially passive became more enthusiastic, were able to systematically explain the digestive process from the mouth to the anus, and demonstrated a significant increase in the class average score. The plasticine learning aid enables multimodal learning that accommodates kinesthetic, visual, and auditory learning styles while fostering creativity, collaboration skills, and students’ fine motor abilities. These findings reinforce that concrete teaching aids based on locally available materials can serve as an effective and economical alternative for improving scientific literacy in elementary schools, particularly in areas with limited technological access. This study contributes to the development of constructivist and experiential learning-based instruction aligned with 21st-century education paradigms and the Merdeka Belajar policy, which emphasizes student independence and creativity.